Meningkatkan Pemasaran Produk Melalui Digitalisasi Konten pada UMKM Camilan Brand Asaa Arpik - Agus Rahmat Santoso; Nizar Fahmy Maulana; Sudarmiatin Sudarmiatin; Yuli Soesetio (FKIP, Universitas Palangka Raya, 2026)
This community service activity aims to improve the digital marketing capabilities of the ASAA Arpik snack MSME through the digitization of content on various digital platforms. The activity partner is the ASAA Arpik MSME owned by Siti Zulaikah located in Sukosari, Gondanglegi, Malang. The main problems faced by the partner include low marketing reach, the absence of a structured digital content ecosystem, suboptimal utilization of WhatsApp Business, the unavailability of a website and Google Business Profile, and the suboptimal use of Instagram, Facebook, TikTok Shop, and marketplaces as promotional and sales media. The implementation method is carried out through mentoring, training, and implementation of digital marketing strategies that include optimizing WhatsApp Business, creating a free Google Business Profile and website, developing a social media content strategy, developing TikTok Shop and marketplaces, and preparing a 30-day digital content calendar. In addition, an evaluation was conducted based on digital indicators such as the number of customer interactions, content reach, and increased sales potential. The results of the activity show that content digitization can improve the digital marketing readiness of MSMEs, strengthen brand identity, expand promotional reach, and increase opportunities for interaction and transactions with customers. This assistance is expected to help ASAA Arpik build a more integrated, consistent, and sustainable digital marketing system so that it can increase the competitiveness of MSMEs in the digital economy era.